Influence of perceived equity, job enrichment, and burnout among educators in Indian private universities on job satisfaction and the desire to quit - Annamalai, Sumathi (Frontiers in Education, 2022)
The desire to quit converts into actual attrition if left unaddressed. Additionally, employees’ job satisfaction strongly influences their desire to stay or leave. Several individual and organizational factors affect job satisfaction levels, all of which must be thoroughly analyzed to curb both the desire to quit and attrition. The current study tests a model associating perceived equity, job enrichment, and burnout with job satisfaction and the desire to quit of educators employed in private universities in India. Data were collected from 272 university faculty members using five scales, namely, job enrichment, perceived equity, employee burnout, job satisfaction, and intention to leave, and were analyzed using AMOS 17. The initial fitness results failed to support the hypothesized framework, but a revised framework yielded a good fit for the data. Results show that perceived equity has a positive influence on job satisfaction (Hypothesis 2), job enrichment positively affects job satisfaction (Hypothesis 3), burnout negatively influences job satisfaction (Hypothesis 4), and job satisfaction negatively affects the desire to leave (Hypothesis 1). Perceived equity, burnout, and job satisfaction were found to mediate the association between job enrichment and the desire to leave. The results indicate that private universities must focus on job satisfaction to reduce employees’ desire to quit, thereby reducing the attrition level, which is currently a severe problem with both financial and non-financial consequences to universities. From the results, it can be seen that job enrichment has acted as a mediator to influence employees’ job satisfaction. Future research can explore HR practices contributing to high job enrichment, and this study would have considerable practical implications.